COVID‐19 lockdown and its latency in Northern Italy: seismic evidence and socio‐economic interpretation (2020)
The Italian Government has decreed a series of progressive restrictions to delay the COVID-19 pandemic difusion in Italy since March 10, 2020, including limitation in individual mobility and the closure of social, cultural, economic and industrial activities. Here we show the lockdown efect in Northern Italy, the COVID-19 most afected area, as revealed by noise variation at seismic stations. The reaction to lockdown was slow and not homogeneous with spots of negligible noise reduction, especially in the frst week. A fresh interpretation of seismic noise variations in terms of socioeconomic indicators sheds new light on the lockdown efcacy pointing to the causes of such delay: the noise reduction is signifcant where non strategic activities prevails, while it is small or negligible where dense population and strategic activities are present. These results are crucial for the a posteriori interpretation of the pandemic difusion and the efcacy of diferently targeted political actions.